Algorithm-Aided BIM 기반 원전 3차원 설계기준 관리시스템 개발 - 신재섭; Shin, Jaeseop (한국건설관리학회 논문집, 20(2), 2019)
The APR1400 (Advanced Power Reactor 1400MW) nuclear power plant is a large-scale national infrastructure facility with a total project cost of 8.6 trillion won and a project period of 10 years or more. The total project area is about 2.17 million square meters and consists of more than 20 buildings and structures. And the total number of drawings required for construction is about 65,000. In order to design such a large facility, it is important to establish a design standard that reflects the design intent and can increase conformity between documents (drawings). To this end, a design bases document (DBD) reflecting the design bases that extracted in regulatory requirements (e.g. 10CFR50, Korean Law, etc.) is created. However, although the design bases are important concepts that are a big framework for the whole design of the nuclear power plant, they are managed in 2-dimensional by the experts in each field fragmentarily. Therefore, in order to improve the usability of building information, we developed BIM(Building Information Model) based 3-dimensional design bases management system. For this purpose, the concept of design bases information layer (DBIL) was introduced. Through the simulation of developed system, design bases attribute and element data extraction for each DBIL was confirmed, and walls, floors, doors, and penetrations with DBIL were successfully extracted. 국내 신형원전 APR1400 (Advanced Power Reactor 1400MW)은 총 사업비 8조 6천억원, 사업기간 10년 이상이 소요되는 대형 국가기반시설이며, 60년 이상 운영되어 국가경제 및 국민의 안전에 밀접한 영향을 끼친다. 또한 총 사업부지 217만$m^2$내 20개 이상의건물 및 구조물로 구성되어 있으며, 건설에 필요한 전체도면은 약 6만5천장에 이른다. 이러한 대형시설의 설계를 위해서는 설계의도를 명확히 규정하여 일관성 있게 설계가 진행될 수 있는 일종의 가이드라인 역할을 하는 설계기준이 필수적이다. 이를 위해 설계기준(Design Bases)을 반영한 설계기준문서(Design Bases Document 또는 Drawing, DBD)를 작성하여, 설계 일관성 및 도면간의 일치성을 유지하고 있다. 하지만 설계기준은 원전 전체 설계에 큰 틀이 되는 중요한 개념임에도 불구하고 각 분야 전문가들에 의해 문서기반(2차원) 및 파편적으로 관리되다보니 후속설계에 정확히 반영되는데 한계가 있었다. 따라서 본 연구에서 시설정보 활용성을 높이기 위해 3차원 정보모델인 BIM (Building Information Model)과 Algorithm-aided BIM을 활용하여, 원전의 최소단위 공간인 실(Room)을 기반으로 한 3차원 설계기준 관리하는 시스템을 개발하였다. 이를 위해 설계기준정보층(DBIL)개념을 도입하였으며, 시뮬레이션을 통해 각 DBIL별 설계기준 속성 및 설계요소 데이터가 연동됨을 확인하였으며, DBIL에 연계되는 벽, 바닥, 문, 관통부 등을 정상적으로 추출하였다.